2016
DOI: 10.5137/1019-5149.jtn.18331-16.2
|View full text |Cite
|
Sign up to set email alerts
|

Supraorbital keyhole microsurgical fenestration of symptomatic temporal arachnoid cysts in children, advantages and limitations.

Abstract: Preoperative clinical presentation of the patients included headache (80%), nausea & vomiting (64%), drug resistant epilepsy (52%), macrocephaly (12%) papilledema (28%), motor weakness in the form of right-sided hemiparesis (12%) and cranial nerve palsy. Postoperative complete subsidence of headache was noted in 50%, while 20% remained unchanged. Drug resistant epilepsy improved in 69% of the patients. Postoperative MRI showed initial decrease in cyst volume as early as 3 months, only in a range of 5-12% volum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 27 publications
0
12
0
Order By: Relevance
“…18,53 In this systematic review, only three cases of CSF rhinorrhea were reported in the pediatric literature out of all studies (2%). 7,44,50 Lastly, development of a pseudomeningocele can be of concern for cosmetic and wound healing reasons. General prevalence postoperatively has been reported to be 0.07% to 2% in adult patients.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…18,53 In this systematic review, only three cases of CSF rhinorrhea were reported in the pediatric literature out of all studies (2%). 7,44,50 Lastly, development of a pseudomeningocele can be of concern for cosmetic and wound healing reasons. General prevalence postoperatively has been reported to be 0.07% to 2% in adult patients.…”
Section: Discussionmentioning
confidence: 99%
“…Skin incisions were made superior to the eyebrow in six studies. 33,34,[41][42][43][44] A skin incision within the hair of the eyebrow was made in nine studies. 7,39,40,[45][46][47][48][49][50] Endoscopic assistance was reported to be used in all patients in eight studies 7,40,41,[43][44][45][46][47][48] and in 25% (2/8) of cases in one study.…”
Section: Qualitative Assessmentmentioning
confidence: 99%
See 3 more Smart Citations